2020
DOI: 10.1002/acr.23923
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis, Sleep Health, and Systemic Inflammation in Older Men

Abstract: ObjectiveTo examine the associations of prevalent arthritis with systemic inflammation in older men and to test whether sleep health mediates the associations.MethodsCross‐sectional data came from 2,562 community‐dwelling older men (all were age 65 years or older; mean age 76 years) in the Osteoporotic Fractures in Men Study who participated in a sleep ancillary study in 2003–2005. Participants were classified as having osteoarthritis (OA) (24%) or rheumatoid arthritis (RA) (0.7%) based on self‐reported diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…We also found a significant inverse association between hs‐CRP and TGF‐β with sleep quality. This finding was in accordance with the studies examining the association between inflammatory markers and sleep health 14,109,110 . It must be kept in mind that sleep disturbances and inflammation have a bidirectional association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found a significant inverse association between hs‐CRP and TGF‐β with sleep quality. This finding was in accordance with the studies examining the association between inflammatory markers and sleep health 14,109,110 . It must be kept in mind that sleep disturbances and inflammation have a bidirectional association.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was in accordance with the studies examining the association between inflammatory markers and sleep health. 14,109,110 It must be kept in mind that sleep disturbances and inflammation have a bidirectional association. Sleep disturbances contribute to weight gain and inflammation by increasing morning level of cortisol, decreasing insulin sensitivity and growth hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Although actigraphy revealed a slightly higher number of nocturnal awakenings in the RA patients, consistent with the results of polysomnographic studies, [1] the RA patients did not report worse sleep quality or fatigue. This is consistent with a recent study, which found that RA was not correlated with poor sleep in male patients aged 65 years or older using a sleep health score measured by self-reporting and actigraphy [34] . Furthermore, in RA, sleep disturbances are thought to primarily stem from pain and depression [3] .…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a recent study, which found that RA was not correlated with poor sleep in male patients aged 65 years or older using a sleep health score measured by self-reporting and actigraphy. [ 34 ] Furthermore, in RA, sleep disturbances are thought to primarily stem from pain and depression. [ 3 ] Although RA patients had a significantly lower SF-36 physical component summary score than healthy controls in this study, they did not report more severe joint pain or impaired mental health, as evidenced by a similar SF-36 mental component summary score.…”
Section: Discussionmentioning
confidence: 99%
“…People with arthritis were reported to have a higher proportion of sleep problems [11,12]. Epidemiological studies had also found correlation between sleep problems and higher risk of arthritis, especially the middle-aged and the elderly [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%